SIMPLE ANALYTICAL METHOD FOR THE SIMULTANEOUS ESTIMATION OF HYDROCHLOROTHIAZIDE AND CANDESARTAN BY RP-HPLC - K., Madhavi; M., Navamani; C., Prasanthi (International Journal of Applied Pharmaceutics, 2017)
Objective: To develop a simple, rapid, economic, accurate and precise reverse phase-high performance liquid chromatographic (RP-HPLC) method for the determination of hydrochlorothiazide and candesartan in the pharmaceutical dosage form and to validate as per international conference on harmonization (ICH) guidelines. Methods: The chromatographic separation was performed on Silanol BDS C18 column (250 x 4.6 mm, 5 Î¼m), a mobile phase consisting of water (pH adjusted to 2.8 with orthophosphoric acid): acetonitrile (30:70 % v/v), with a flow rate 1 ml/min and the detection wavelength of 210 nm using photodiode array (PDA) detector. Results: The developed method resulted in elution of hydrochlorothiazide at 2.28 min and candesartan at 4.28 min. The calibration curves were linear (r2=0.999) in the concentration range of 6.25-18.75 Î¼g/ml and 8-24 Î¼g/ml for hydrochlorothiazide and candesartan respectively. The percentage recoveries were found to be 99.78-100.39 for hydrochlorothiazide and 99.87-100.64 for candesartan. The limit of detection (LOD) was found to be 0.410 Î¼g/ml and 0.699 Î¼g/ml for hydrochlorothiazide and candesartan respectively. The limit of quantitation (LOQ) was found to be 1.367 Î¼g/ml and 2.330 Î¼g/ml for hydrochlorothiazide and candesartan respectively. Conclusion: A simple, economic, accurate, precise, linear and rapid RP-HPLC method was developed for simultaneous quantitative estimation of hydrochlorothiazide and candesartan in bulk and pharmaceutical formulation and the method was validated as per ICH guidelines. Hence, the method holds good for the routine analysis of hydrochlorothiazide and candesartan in various pharmaceutical industries as well as in academics.